(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: People with MRS usually have mild pyramidal symptoms with fever, headache, stiff neck, and urgency. The bladder isinitially flexible, but as the disease progresses it becomes either normal or hyperflexible with frequent urodynamics. MRS, a less severevariation of acute disseminated encephalomyelopathy (ADM), is characterised by a rise in the number of cells, total protein, andsometimes myelin basic protein in the cerebrospinal fluid. A exceptional combination of acute urinary retention and aseptic meningitishas been proposed. Patients with this condition exhibits mild pyramidal involvement with no other deformities.The main focus is toportray this syndrome by analysing literatures.Methods:A 70 year old male presented with complaints of fever, increased duration and frequency on urination with the background ofEpstein Barr virus infection and is a known hypertensive not on treatment. He lacked any other risk factors for Meningitis retentionsyndrome.Results:Approach to this case is helpful with symptoms of urinary complaints with progression to choreiform complaints . EBV antibodytitre found to be elevated found to be the cause of EBV reactivation in this case.Conclusion:This condition might go misdiagnosed with similar conditions mimicking meningitis retention syndrome. Hence severalstrategies has to be applied in diagnosing and treating the root cause of MRS.